Microbiomes in supragingival biofilms and saliva of adolescents with gingivitis and gingival health - Wirth, Roland; Maróti, Gergely; Lipták, Lídia; Mester, Mónika; Al Ayoubi, Alaa; Pap, Bernadett; Madléna, Melinda; Minárovits, János; Kovács, Kornél L. (Oral diseases, 2022)
Background Important alterations exist in the microbiomes of supragingival biofilm and saliva samples from adolescent patients developing induced or spontaneous gingivitis relative to healthy controls. These and the relationships to dental health are not fully understood yet. Subjects and Methods Supragingival biofilm samples (n = 36) were collected from the teeth of 9 adolescents with gingivitis induced by orthodontic appliances, as well as dental plaques (n = 40) from 10 adolescents with spontaneous gingivitis, in addition to similar samples (n = 36) from 9 healthy controls. The bacterial metagenomes were analyzed by 16S rRNA gene amplicon sequencing. Salivary microbiomes of the same persons were characterized by shotgun metagenome sequencing. The data sets were examined using advanced bioinformatics workflows and two reference databases. Results The composition and diversity of bacterial communities did not differ extensively among the three study groups. Nevertheless, the relative abundances of the genera Fusobacterium, Akkermansia, Treponema, and Campylobacter were prominently higher in gingivitis patients versus controls. In contrast, the genera Lautropia, Kingella, Neisseria, Actinomyces, and Rothia were significantly more abundant in controls than in either of the two gingivitis groups. Conclusions The abundance pattern of certain taxa rather than individual strains shows characteristic features of potential diagnostic value. Stringent bioinformatics treatment of the sequencing data is mandatory to avoid unintentional misinterpretations.